Factors influencing livestock ownership and herd intensity among smallholder farmers in the Eastern Cape, South Africa - Jabulile Z. Manyike; Amon Taruvinga; Leocadia Zhou (Heliyon)
This study explores the factors influencing smallholder farmers' decisions on livestock ownership and herd size in the context of climate change. A cross-sectional approach was employed, using a multi-stage sampling method to survey 600 smallholder farmers, 495 of whom were engaged in livestock production. Data were collected through a semi-structured questionnaire and analysed using a double hurdle model. The findings reveal that the decision to own livestock is positively influenced by adherence to African traditional religion, access to climate information, membership in farming organizations, income diversification, possession of formal housing, exposure to high average temperatures, and the likelihood of being in female-headed households. In contrast, higher educational attainment and larger household sizes are associated with a lower likelihood of livestock ownership. The intensity of livestock herd is positively influenced by male-headed households, farm organization affiliation, access to diversified income streams, and higher average annual precipitation. While male-headed households are less likely to engage in livestock ownership initially, those that do, tend to have larger herds. The study concludes that both household capital and environmental factors significantly shape smallholder farmers’ livestock ownership decisions. The findings suggest that smallholder farmers in the study area may increasingly rely on livestock as a sustainable and adaptive strategy in response to changing temperature patterns and evolving socio-economic needs. Based on these findings, policy recommendations include promoting gender-inclusive livestock policies to empower female-headed households, enhancing access to climate information, supporting farm organizations and income diversification, and fostering adaptation to environmental changes, to improve the sustainability and resilience of smallholder livestock farming.